Investigating characteristics of the long-term settlement of railway embankments in warm permafrost areas - Xu, Yuezhen; Shen, Mingde; Zhou, Zhiwei; Ma, Wei; Li, Guoyu; Chen, Dun (Frontiers in Environmental Science, 2023)
The embankment in the permafrost zone of Qinghai-Tibet Railway(QTR) faces the problem of permafrost degradation, especially in the warm and ice-rich permafrost areas. The settlement deformation of the embankment are more serious in this areas. This study systematically investigates the settlement deformation characteristics during 16 operational years of three types of typical roadbed structures. Traditional embankment (TE), U-shaped crushed rock embankment (UCRE), and crushed rock revetment embankment (CRRE) are inclounded the roadbed structures. The long-term monitoring ground temperature and deformation data of the embankment section along the QTR in warm permafrost areas from 2005 to 2020 are utilized to analysis. It focuses on the influence law of roadbed structure form, shaded slope effect, and temperature field change on the settlement of the roadbed. The results indicated that the two types of crushed rock embankment (CRE) of the long-term cumulative settlement are less than 50% of the cumulative settlement of the TE, and the impact on controlling settlement is significant. The annual settlements of the three types of embankment structures are related to the artificial permafrost table (APT) and influenced by cyclical climate change at the regional scale. The annual growth rate of settlement of the left and right shoulders of the UCRE as a result of the effect of shady-sunny slopes does not vary considerably as the number of operational years increases. The impact of shady-sunny slopes on the CRRE for the various settlements before 2008 was negligible. After 2008, the thermal disturbance to the embankment temperature field induced by the preconstruction and the effect of shady-sunny slopes decreased gradually as the number of operational years rose. In some years of operation, a melting interlayer in the TE and CRRE greatly affected the embankment settlement acceleration. The settlement growth rate of the TE is related to the downward direction of the artificial permafrost table (APT). During the operational years, there was no melting interlayer in the UCRE. The development of the settlement rate is unaffected by the temperature field for either the left or right embankment shoulder.